1987
DOI: 10.1113/jphysiol.1987.sp016356
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine receptors and sodium channels in denervated and botulinum‐toxin‐treated adult rat muscle.

Abstract: SUMMARY1. The number of acetylcholine (ACh) receptors and Na channels was measured in adult rat hind-limb muscles after denervation or injection of botulinum toxin type A (BoTX), using specific binding of radiolabelled neurotoxins. 5. It was concluded that neuromuscular blockade with BoTX is equivalent to denervation in its effects on synthesis of ACh receptors. Numbers of Na channels are more stable than ACh receptors but may also be modulated by neuromuscular activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 52 publications
3
11
0
1
Order By: Relevance
“…BoNT exposure of limb skeletal muscle causes a trend toward larger motor endplates, but the overall size was not significantly different from that of controls (Bambrick and Gordon, 1987;Alderson et al, 1991;Witzemann et al, 1991;Ma et al, 2004). Similarly, our results of developing EOM indicate that BoNT induced a tendency, although not significant, for increased surface area of the motor endplates.…”
Section: Endplate Morphology and Terminal Sprouting Was Moderately Afsupporting
confidence: 64%
“…BoNT exposure of limb skeletal muscle causes a trend toward larger motor endplates, but the overall size was not significantly different from that of controls (Bambrick and Gordon, 1987;Alderson et al, 1991;Witzemann et al, 1991;Ma et al, 2004). Similarly, our results of developing EOM indicate that BoNT induced a tendency, although not significant, for increased surface area of the motor endplates.…”
Section: Endplate Morphology and Terminal Sprouting Was Moderately Afsupporting
confidence: 64%
“…A reduction in acetylcholine esterase levels leads to increased receptor sensitivity (24). There is upregulation of extrajunctional acetylcholine receptors along with increased lysosomal and endocytic activity, which may contribute to recovery (1,23). In animal studies sprouting of new terminal axons from affected motor nerves has also been seen.…”
Section: Recovery From the Effects Of Toxinmentioning
confidence: 90%
“…It has been reported that the number and distribution area of acetylcholine receptors were increased in rat diaphragm [21] and hindlimb [22] after treatment with high-dose BoNT. In the present case of low-dose intoxication, however, we consider that increases in the number and distribution area of effective acetylcholine receptors do not contribute significantly, at least not at the parent motor nerve terminals.…”
Section: Postsynaptic Remodelingmentioning
confidence: 99%